FAKTOR SOSIODEMOGRAFI DENGAN KELANGSUNGAN HIDUP BAYI DI INDONESIA (ANALISIS DATA SDKI 2007) - Utami Dewi (Jurnal Ilmiah Manuntung, 2015)
It is recommended for a mother to initiate to give early breastfeeding for a newborn as the first breast milk is known to be nutritious and contains antibody. The delay of breastfeeding shows that non breast milk-supplementary food is given. Based on BPS and Macro International data 65% of infants received pre-lacteal feeds besides breast milk in their three days of life.The known relationship between sociodemography and infants’ survival in Indonesia.This was an observational study with a cohort retrospective study design by using IDHS data year 2007. Samples were all infants (<12 months, breastfed after birth) from mothers aged 15-49 years old as many as 15.679 mothers. The independent variable was sociodemography and the dependent variable was infants’ survival. The analyses used univariable, bivariable, and survival analysis with Kaplan-Meier and Log regression. Bivariable analysis using survival Kaplan-Meier showed that there was significant relationship between mother age with Log Rank 15,89 and p<0,05, mother education with Log Rank 16,25 and p<0,05 , place of residence with Log Rank 18,84 and p<0,05, socioeconomic with Log Rank 38,71 and p<0,05, birth attendant with Log Rank 17,35 and p<0,05 and infants’ survival. Sociodemography  was associated significant with an infant survival. Other factors affecting infant’s survival were birth attending with no professional and mother’s age <20 and ≥35 years old.